AGAMA DAN NEGARA : POLITIK IDENTITAS MENUJU PILPRES 2019 - Saputro, Agus (P3M IAIN KEDIRI, 2018)
Indonesia is a democratic country in carrying out its government. Elected Indonesian Presidents in a variety of ways, namely elected by parliament, and by direct elections through elections. Religious relations in state life in Indonesia, especially in political activities cannot be separated. Religion and politics share the role of the institution of regulation and maintaining value. In acts of religious politics are often used as vehicles to win political battles or elections. In carrying out political activities, state authority becomes the highest authority. Religion in politics is under the state whose role is to unite state authority with social power.